Screening for antimalarial activity of crude extracts from African medicinal plants - Ramalhete, Cátia (2012)
Malaria a serious parasitic disease, spread by mosquitoes from Anopheles species, is still the most devastating in the world. It has been estimated that in the last 20 years mortality from malaria has doubled (it is currently 3 millions deaths annually), and a major factor responsible for this increase is the resistance of malaria parasites to antimalarial drugs.1 Consequently, there is an urgent need to discover new and affordable antimalarials. Antimalarial drugs derived from plants appear to be promising therapeutic candidates as exemplified by artemisinin and quinine, two of the most effective drugs against Plasmodium falciparum. In Africa, up to 80% of the population use traditional medicines for primary health care.2 However, few scientific data are available to validate the antimalarial properties of medicinal plants. The aim of this study was to carry out a scientific evaluation of the claimed antimalarial properties of plants used in traditional medicine against malaria and fever, in order to validate their use and to determine their potential as new sources of antimalarial drugs.